(untitled) (Symposium on Natural and Applied Sciences, 2026)
Liver fibrogenesis in chronic hepatitis C (CHC) involves not only inflammation-driven hepatocyte damage but also pathological angiogenesis and extracellular matrix remodeling [1]. Vascular endothelial growth factor A (VEGFA) is the principal regulator of new vessel formation. Under conditions of chronic liver injury, activated hepatic stellate cells and inflammatory cells produce VEGFA, stimulating the growth of pathological vessels within fibrous septa and promoting portosystemic shunting [2]. The C936T polymorphism (rs3025039) is located in the 3′-untranslated region of the gene and affects mRNA stability, thereby modulating VEGF protein levels. Matrix metalloproteinase-9 (MMP-9) is a zinc-dependent enzyme that degrades type IV collagen, gelatin, and laminin, making it a key mediator of basement membrane and connective tissue remodeling [3]. The Gln279Arg polymorphism (rs17576) involves the catalytic domain and determines proteolytic activity. The biological rationale for studying both loci simultaneously is that neovascularization requires prior matrix degradation by MMP-9 [4].